СONSTRUCTION AND THE ALGORITHM OPERATION OF THE LASER COMBINED FIRE DETECTOR - A. I. Kitsak; A. P. Lushchyk; D. L. Esipovich; V. N. Konon; I. V. Kavalchyk; O. A. Protasevich; I. B. Tretyak (Приборы и методы измерений)
The point optical smoke detector is currently the most effective means of fire detection at the early stage of its occurrence. The urgent task for this type of detector is to increase its sensitivity to «black» smoke and ensure resilience to the effects of electromagnetic interference and particle smoke origin.The objective of this work is to develop a structure and algorithm of point combined fire detector that provides high sensitivity to various types of fumes, detection rate and high noise immunity. The decision of the current objective is carried out using the proposed optical scheme of the dual-channel devices of smoke detection (for control of the radiation intensities scattered by smoke particles and passed through the smoke).The design and algorithm of the combined fire detector comprising a dual-channel laser device of smoke detection and carbon monoxide detector is developed.The results of the made detector tests indicate about its increased in comparison with the conventional single-channel point smoke fire detector sensitivity to various types of fumes and detection rate of fires. The high functional characteristics of the detector are provided with application additional channel of smoke detection (to intensity change of transmitted radiation through it) created by the requirements for unrestricted entry of smoke in the area of control and effective algorithm for processing of recorded signals.